Christianity and fundamental human rights in Nigeria (2012)
The Issue of human rights’ abuse in Nigeria has been discussed in various fora from political, social, economic and judicial viewpoints. While efforts made in these fields of academic endeavour are highly commendable, one area which seems to have been largely ignored is the religious response to the subject matter. This paper is aimed at discussing the issue of human rights from a Christian perspective with emphasis on what Christian organizations should do in the quest for the promotion of human rights in Nigeria. The Nigerian constitutions since independence have been embodying the provisions of human rights. Unfortunately, these provisions are not strictly adhered to; and this has accounted for lack of good governance in Nigeria. In achieving the aim, therefore, we shall discuss issues relating to human rights abuse, various cases of abuse in Nigeria, and what should be the attitude and efforts of Christians.